Evaluasi Daya Tarik (Attraction) Klenteng Sam Poo Kong Berdasarkan Kepuasan Pengunjung - Ratna Ayu Permatasari Arief Rahman; Nova Oktaviana Hestika (Universitas Batanghari Jambi, 2026)
This study aims to assess how strongly Sam Poo Kong Temple’s attractions draw visitor interest. The approach uses the 4A concept, focusing on the attraction variable. Data were collected through observation and questionnaires from 96 respondents, then analyzed using the Customer Satisfaction Index (CSI). The results indicate that key physical attractions such as the unique architecture, the historic statue and reliefs, and cultural activities like lion dance and the Cheng Ho procession, are the main strengths that attract visitors. Overall, Sam Poo Kong Temple’s attractions have strong potential as a tourism magnet. However, to sustain and increase visitor interest, improvements are needed in the promotion and scheduling of cultural attractions, staff training to make services friendlier and more informative, and efforts to maintain the site’s authenticity and cleanliness. With these improvements, Sam Poo Kong Temple is expected to provide a more satisfying and sustainable cultural tourism experience.